Pengaruh Lama Perendaman Dalam Larutan Chlorhexidine Terhadap Perubahan Warna Resin Akrilik Heat Cured - Irsan Ibrahim; Ferry Jaya; Prima Luthfia; Dinis Purnamaning Ayu Izzati (Jurnal Material Kedokteran Gigi, 2016)
Denture base acrylic resin should have a natural color, like the color of the oral tissues. Color stability is one of the most important features of a dental material, because of discoloration is a sign of aging and damage of these materials. According to some studies it takes 15 minutes to a solution of chlorhexidine eliminate the fungus Candida albicans effectively. But how about discoloration on acrylic base itself. Discoloration indicates a change value of the color group that hue, chroma and value. The purpose of this study was to determine the effect of immersion time chlorhexidine against heat cured acrylic resin. The materials used are heat cured acrylic resin and total specimens totaling 21 pieces divided into 3 groups of the time, a group of 15 minutes, 30 minutes and 45 minutes. Each group consists of 7 pieces of specimens and each specimen measured value of hue, value and chrome. Acrylic resin colors checked after soaking with Vita Easy Shade tool. There were significant differences in color chrome heat cured acrylic resin is immersion in chlorhexidine solution between 30 minutes to 45 minutes. Immersion heat cured acrylic resin in solution khlorheksiden up to 45 minutes causes the color heat cured acrylic resin is more faded. Users denture acrylic for more attention to color changes that occur in the base when he often used chlorhexidine mouthwash.